Green Finance and Economic Growth in Emerging Markets: A SWOT Analysis - Zarrad, Olfa; Gafsi, Nesrine (Journal of Ecohumanism, 2025)
This paper explores the critical intersection of green finance and economic growth in emerging markets through a SWOT analysis framework. As global economies increasingly pivot towards sustainable development understanding the dynamics of green finance becomes essential, particularly in regions where financial systems are adapting to environmental challenges. The study reviews existing literature on the role of green finance in promoting economic growth examining factors such as agricultural CO2 emissions, renewable energy integration, and the impact of financial development. Key findings suggest that while green finance presents significant opportunities for fostering sustainable economic growth, it also faces challenges such as regulatory barriers, limited access to financing, and need for robust institutional frameworks. This analysis aims to provide insights into how emerging markets can leverage green finance to drive economic prosperity while addressing environmental concerns, ultimately contributing to the broader goals of sustainable development.